The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11306-018-1421-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of species and environmental effects on rhubarb roots metabolome using 1H NMR combined with high performance thin layer chromatography

Abstract: IntroductionThe pharmacological activities of medicinal plants are reported to be due to a wide range of metabolites, therein, the concentrations of which are greatly affected by many genetic and/or environmental factors. In this context, a metabolomics approach has been applied to reveal these relationships. The investigation of such complex networks that involve the correlation between multiple biotic and abiotic factors and the metabolome, requires the input of information acquired by more than one analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Our preliminary results demonstrated that chemical analysis and DL measurements were not able to segregate of rhubarb samples (both commercial and wild samples) according to difference in sub-species. Ge et al reported the same results using PCA to analyze the 1 H NMR data of different rhubarb sub-species samples [33]. This data may support the idea why in Chinese pharmacopeia, different sub-species were collected because of their similarity in chemical composition thought with difference sub-species.…”
Section: Discussionmentioning
confidence: 59%
“…Our preliminary results demonstrated that chemical analysis and DL measurements were not able to segregate of rhubarb samples (both commercial and wild samples) according to difference in sub-species. Ge et al reported the same results using PCA to analyze the 1 H NMR data of different rhubarb sub-species samples [33]. This data may support the idea why in Chinese pharmacopeia, different sub-species were collected because of their similarity in chemical composition thought with difference sub-species.…”
Section: Discussionmentioning
confidence: 59%
“…The confirmation of the chemical structures of compounds in these bands can be resolved with further spectrometric analysis, like MS or NMR. Thus, the hyphenation of HPTLC as an efficient automatic sample preparation technology with NMR and MS (LCor GC-MS) has proved to be highly useful for metabolomic studies [18,20]. However, some of the limitations related to structural features of saponins do persist, since they tend to bind strongly to the silica sorbent and show low sensitivity in LC-MS analysis requiring hydrolysis for GC-MS.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic variation of plants is largely mediated by both genetic and environmental factors [20,21]. Similar to many other medicinal plants, O. japonicus roots are currently grown in several locations across China.…”
Section: Introductionmentioning
confidence: 99%
“…tanguticum is mainly distributed in Qinghai, Sichuan, and Gansu provinces and in the region to the east of the Tibet Autonomous Region at an altitude ranging from 2000 m to 4600 m. Studies have shown that the quality of Rh. tanguticum varies among different geological origins [ 8 , 9 ], which can be attributed to environmental variations such as altitude [ 10 ] or other climate and soil factors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%